Toxicity of Quaternary Mixture of Formulated Glyphosate and Phenols on Providencia vermicola Dehydrogenase Activity - Franca Ngozi Okafor; Michael Uchenna Orji; Christian Okechukwu Nweke; Samuel Chinedu Onuorah; Bright Obidinma Uba; Chinweike Unoma Dokubo (Archives of Current Research International, 2021)
Aims: To assess the toxicity of glyphosate (as an active ingredient in drysate), three phenols (2,4-dichlorophenol, 4-chlorophenols and phenol) and quaternary mixtures of glyphosate, 2,4-dichlorophenol, 4-chlorophenol and phenol on the dehydrogenase activity (DHA) of P. vermicola. Study Design: The glyphosate, 2,4-dichlorophenol, 4-chlorophenol and phenol mixture ratios (%) were designed as: 25%:25%:25%:25%; 30%:20%:20%:30%, 40%:10%:10%: 40%; 50%:5%:30%:15% and 20%:20%:10%:50% for the respective mixtures in the concentration range of 0-1000 mg/L. Place and Duration of Study: Silver Press Laboratory, Owerri Nigeria between July, 2016 and August, 2019. Methodology:A laboratory scale study was carried on four toxicants using dehydrogenase inhibition test. The inhibition of dehydrogenase activity of the isolate by toxicant was calculated relative to the control. The percentage inhibition data generated was fitted into a logistic dose response model and Weibulleum to obtain their respective IC50. Results:The results revealed that the median inhibitory concentrations (IC50) of the mixtures on the Providencia vermicola were 247.17 ±10.20, 163.44 ± 8.18, 251.33 ± 45.25, 267.30 ± 8.76 and 178.93 ± 45.53 mg/L, respectively. Toxicity index (TI) model was used to evaluate the joint action toxicity of the mixtures on the test organism and was 60 % antagonistic. Conclusion: Thus, these synergistic and additive interactions of formulated glyphosate with the intermediates of 2,4-D was possible against the dehydrogenase activity of Providenciavermicola an important plant growth promoting bacterium. The dynamics of the toxic effects thus would depend on the concentration of the compounds.